La relación entre las denuncias en la Contraloría General de la República y la eficiencia del gasto público en las regiones del Perú durante el periodo 2008 - 2019 - Rospigliosi Cruz, Justo Martín (2022)
In Peru, corruption is a very serious social problem that has deep roots for more than 30 years and has become a social disease today, it has corrupted even the poorest citizens. Corruption in 2019 cost Peru 23,227 million soles to the Peruvian State, which could be invested in social programs, education, or improvement of health services, helping to reduce the country's social gaps. The Office of the Comptroller General of the Republic examines the accounts of public institutions, in order to ensure the legality of income, expenses and integrity of state assets. In this sense, the present research aims to determine, study and analyze the relationship between the complaints registered in the Comptroller's Office and the efficiency of public spending in the departments of Peru; To do this, we opted for a non-experimental, quantitative and correlational-level investigation, in which we used a multiple regression model to find the relationship of our study variables. Among the main conclusions we find a positive and statistically significant relationship between the complaints registered by the comptroller and the efficiency of public spending in the departments of Peru, more specifically an increase in a complaint would increase the efficiency of public spending by 0.45%. We also find a positive correlation of economic growth, income per capita and income of the commerce sector towards the efficiency of public spending and a negative relation between this and the level of unemployment.The results found in the present study allow us to confirm the general hypothesis and the specific hypotheses raised and allow us to have a more complete knowledge of the importance of the efficiency of public spending for the national economy and especially in regional economies.